2010
DOI: 10.3390/ijms11082910
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Cardiac Tissue Rings Using a Magnetic Tissue Fabrication Technique

Abstract: Here we applied a magnetic force-based tissue engineering technique to cardiac tissue fabrication. A mixture of extracellular matrix precursor and cardiomyocytes labeled with magnetic nanoparticles was added into a well containing a central polycarbonate cylinder. With the use of a magnet, the cells were attracted to the bottom of the well and allowed to form a cell layer. During cultivation, the cell layer shrank towards the cylinder, leading to the formation of a ring-shaped tissue that possessed a multilaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…Significant higher force was observed above 14% strain applied. Moreover, cells were densely packed and formed gap junction within the tissue which was confirmed by immunohistological analysis [188]. This stretchable property can be used to elongate the cells in the longitudinal direction, which can lead to tissue development with greater contractility [189].…”
Section: Cardiac Tissue Engineeringmentioning
confidence: 68%
See 1 more Smart Citation
“…Significant higher force was observed above 14% strain applied. Moreover, cells were densely packed and formed gap junction within the tissue which was confirmed by immunohistological analysis [188]. This stretchable property can be used to elongate the cells in the longitudinal direction, which can lead to tissue development with greater contractility [189].…”
Section: Cardiac Tissue Engineeringmentioning
confidence: 68%
“…8 cm/s) between cardiomyocytes within the cadiomyocyte sheet [148]. Another study showed potential use of Mag-TE in combination with ECM-mimicking technique for the fabrication of cardiac tissue ring [188]. The technique utilized mixture of type I collagen solution and commercially available Matrigel basement matrix (product of BD Biosciences, USA) in an optimized ratio, which was added to MCLs-labeled cardiomyocyte cell suspension.…”
Section: Cardiac Tissue Engineeringmentioning
confidence: 99%
“…By manipulating the strength, shape, and orientation of the magnetic field, multi-directional cell arrangements can be produced in vitro and even directly in vivo. 34 Akiyama et al 35 applied a magnetic force-based tissue engineering technique to cardiac tissue fabrication. A mixture of extracellular matrix precursor and cardiomyocytes labeled with magnetic nanoparticles was added into a well containing a central polycarbonate cylinder.…”
Section: Magnetic Cell Patterningmentioning
confidence: 99%
“…The major advantage of the Mag-TE technique is the induction of cell-dense tissues mimicking native tissues, as demonstrated in the fabrication of cardiomyocyte, 40 myoblast cell sheets 36 and muscle tissues. 34 Okochi et al 37 fabricated a 3D cell patterning culture system using an external magnetic force and a pin holder, which enables the assembly of the magnetically labeded cells on the collagen gel-coated surface as array-like cell patterns, resulting in the development of a 3D in vivo culture model. The cells embedded in type I collagen showed a compacted, spheroid like configuration at each spot, and distinct, accelerated cell growth was observed in cancer model cells compared with control cells.…”
Section: Magnetic Cell Patterningmentioning
confidence: 99%
“…Moreover, the tissue fabrication technique utilizing the magnetic nanoparticles described by the group of Ito et al [84] was recently tested in vitro for yet another cardiovascular application, namely, the cardiac tissue engineering. A mixture of collagen, Matrigel basement matrix, and cardiomyocytes labeled with the magnetic nanoparticles was added into a well containing a central polycarbonate cylinder.…”
Section: Vascular Tissue Engineering With Nanoparticlesmentioning
confidence: 99%